Activity of Topotecan 21-Day Infusion in Patients with Previously Treated Large Cell Lymphoma: Long-term follow-up of an Eastern Cooperative Oncology Group Study (E5493) - Wiernik, Peter H. (2012)
The purpose of this study was to determine the activity of topotecan given by 21-day continuous infusion in patients previously treated with one prior therapy for a diffuse large cell lymphoma or immunoblastic lymphoma. Patients with appropriate histology and measurable disease who had been treated with one prior chemotherapy regimen were eligible for study. Slides of tumor biopsies were submitted for central review of pathology. Patients were required to have ECOG performance status of 0, 1, or 2 and adequate bone marrow function. Patients were treated with continuous infusion topotecan, 0.4 mg/m(2)/day × 21 days. Therapy could be escalated to 0.5 and then 0.6 mg/m(2)/day in subsequent cycles if there was no dose limiting toxicity at the initial dose level. Patients were treated with 2 cycles after achieving complete response or until disease progression or unacceptable toxicity occurred. Thirty seven patients were enrolled, however, only 26 cases were eligible due to performance status of > 2 (2), more than one prior chemotherapy (1), and wrong histology on review (8). Due to the unexpectedly high ineligibility rate, two sets of analysis were done for all the 37 patients enrolled and for the 26 eligible patients, respectively. Of the 37 patients (15 males and 22 females), international prognostic index included 11% low risk, 30% low-intermediate risk; 46% high-intermediate risk, and 8% high risk. The median follow up was 77 months. A total of 136 cycles of therapy were given with a median of 3 cycles per patient. Grade 4 toxicities included: 14% grade 4 thrombocytopenia; 14% grade 4 granulocytopenia, 8% leukopenia, 3% each anemia, hemorrhage, infection, vomiting, thrombosis, liver toxicity, and neuromotor toxicity. The response analysis including all 37 patients showed 5 complete remissions (CR) and 4 partial remissions (PR) for a total response rate of 24% (90% two-stage confidence interval 13–39%). Median progression free survival (PFS) was 3.7 months, with one and two year PFS of 21% and 6% respectively (90% confidence interval 11–34% and 2–15%). Median overall survival (OS) was 10.5 months, with one and two year OS 41% and 27% respectively (90% confidence interval 27–53% and 16–39%). Analysis including only eligible patient showed similar response rates and survival outcomes. Single agent topotecan has moderate activity for previously treated high grade lymphoma equivalent to that of several newer agents, and should be considered for incorporation into multi-drug salvage chemotherapy programs.